1988
DOI: 10.1096/fasebj.2.11.2456243
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action of calcium‐mobilizing agonists: some variations on a young theme

Abstract: It is now accepted that many hormones and neurotransmitters exert their effects through G protein-mediated activation of a phospholipase C, which breaks down phosphatidylinositol bisphosphate. This releases inositol trisphosphate, which mobilizes intracellular calcium, and diacylglycerol, which, in turn, activates protein kinase C. However, recent evidence indicates that other mechanisms are involved. In some cells, the increases in cytosolic calcium elicited within 1-2 s by high concentrations of agonists or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(71 citation statements)
references
References 36 publications
5
65
0
1
Order By: Relevance
“…1). It has been suggested that production ofDAG, the endogenous activator ofprotein kinase C, may result not only from the hydrolysis of polyphosphoinositides but of other phospholipids (e.g., phosphatidylcholine) as well (30). It is important to note, therefore, that pretreatment with ClPheScAMP inhibits EGF-stimulated DAG production (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…1). It has been suggested that production ofDAG, the endogenous activator ofprotein kinase C, may result not only from the hydrolysis of polyphosphoinositides but of other phospholipids (e.g., phosphatidylcholine) as well (30). It is important to note, therefore, that pretreatment with ClPheScAMP inhibits EGF-stimulated DAG production (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…As activation of PLC results in hydrolysis of not only phosphatidylinositol bisphosphate but of phosphatidylinositol monophosphate and phosphatidylinositol as well (and perhaps other phospholipids, e.g., phosphatidylcholine) production of DAG, on a molar basis, is likely to exceed productionof IP3 (30). Therefore, inhibition of AC by concentrations of EGF below the threshold for detectionofIP3 production itself suggests that the inhibition is a consequence of DAG production.…”
Section: Resultsmentioning
confidence: 99%
“…Additional physiological studies linking second messengers to ion transport activities and assays of endogenous levels of InsP3 and diacylglycerol are required to further define the roles of these second messengers in guard cells. Diacylglycerol can be formed from phosphatidylinositol 4-phosphate, phosphatidylinositol, or phosphatidylcholine without concomitant production of InsP3, and temporal differences in levels of InsP3 and diacylglycerol have been noted (6). Steady-state stomatal aperture, which reflects a balance between opening and closing processes (15,28), may be determined by the relative quantities and actions of diacylglycerol and InsP3 present under a given environmental condition.…”
Section: Resultsmentioning
confidence: 99%
“…Diacylglycerol is produced endogenously via several biochemical pathways, including hydrolysis ofthe phosphatidylinositols and phosphatidylcholines (6). In animal systems, diacylglycerol activates a Ca2+-and phospholipid-dependent kinase, protein kinase C (PKC).…”
mentioning
confidence: 99%
“…The hepatic actions of the Ca2" mobilizing agonists have been intimately associated with their ability to increase the intracellular concentration of free cytosolic Ca2" and the subsequent activation of Ca2"-dependent processes (Williamson et al, 1985;Exton 1988). However, work showing that alagonists may activate hepatic functions under Ca2" loading conditions that precluded any further significant increase in the cytosolic free Ca2" concentration (Buxton et al, 1982;Garcia Sainz & Hernandez-Sotomayor, 1985;Saz et al, 1989), supported the operation of a free cytosolic Ca2+-independent branch of the signalling pathway.…”
Section: Discussionmentioning
confidence: 99%